Genome‐wide association study reveals a novel locus for asthma with severe exacerbations in diverse populations. Issue 1 (14th September 2020) - Herrera‐Luis, Esther; Espuela‐Ortiz, Antonio; Lorenzo‐Diaz, Fabian; Keys, Kevin L.; Mak, Angel C. Y.; Eng, Celeste; Huntsman, Scott; Villar, Jesús; Rodriguez‐Santana, Jose R.; Burchard, Esteban G.; Pino‐Yanes, Maria
Abstract: Background: Severe asthma exacerbations are a major cause of asthma morbidity and increased healthcare costs. Several studies have shown racial and ethnic differences in asthma exacerbation rates. We aimed to identify genetic variants associated with severe exacerbations in two high‐risk populations for asthma. Methods: A genome‐wide association study of asthma in children and youth with severe exacerbations was performed in 1283 exacerbators and 2027 controls without asthma of Latino ancestry. Independent suggestive variants ( P ≤ 5 × 10 −6 ) were selected for replication in 448 African Americans exacerbators and 595 controls. Case‐only analyses were performed comparing the exacerbators with additional 898 Latinos and 524 African Americans asthma patients without exacerbations, while adjusting by treatment category as a proxy of asthma severity. We analyzed the functionality of associated variants with in silico methods and by correlating genotypes with methylation levels in whole blood in a subset of 473 Latinos. Results: We identified two genome‐wide significant associations for susceptibility to asthma with severe exacerbations, including a novel locus located at chromosome 2p21 (rs4952375, odds ratio = 1.39, P = 3.8 × 10 −8 ), which was also associated with asthma exacerbations in a case‐only analysis (odds ratio = 1.25, P = 1.95 × 10 −3 ). This polymorphism is an expression quantitative trait locus of the long intergenic non‐protein coding RNA 1913 ( LINC01913 ) in lung tissues ( P = 1.3 × 10 −7 ) and influences methylation levels of the protein kinase domain‐containing cytoplasmic ( PKDCC ) gene in whole‐blood cells ( P = 9.8 × 10 −5 ). Conclusion: We identified a novel susceptibility locus for severe asthma exacerbations in Hispanic/Latino and African American youths with functional effects in gene expression and methylation status of neighboring genes. Abstract :